Predicting of Ukrainian Horticulture Market Development - Sokil, Yana (Видавництво Львівської політехніки, 2013)
For determination of community needs in garden-stuffs and berries for period 2012-2015 it is suggested to carry out prediction of consumption level of horticulture products by the construction of neuron network on the basis of architecture “8-4-1” multilayered perceptron. Initial and predicted rows of consumption level of horticulture products with the purpose of possibility exposure of the predicted volumes of horticultural products consumption for period 2012-2015 and used for development of horticulture market strategy were compared in article. Information of State Statistic Service of Ukraine and authors’ calculations is not confirmed by the prediction results of horticulture production in 2015, which are presented by The Ukrainian Branch Program of Horticulture Development till 2025.
Keywords: horticulture production consumption; neural architecture; multilayered perceptron; market of horticulture products; government support